Dietary diversity and associated factors among lactating women in Ethiopia: Cross sectional study - Wondwosen Molla; Nebiyu Mengistu; Derebe Madoro; Dawit Getachew Assefa; Eden Dagnachew Zeleke; Ruth Tilahun; Yesuneh Bayisa; Meiraf Daniel Meshesha; Getnet Melaku Ayele; Robel Hussen Kabthyme; Asrat Alemu; Mesfin Abebe; et al. (Elsevier, 2022)
Introduction: Lactating women are more vulnerable to malnutrition due to increased physiological demands, the lactogenesis process, consuming an undiversified monotonous diet, and increased nutrient needs during lactation. However, meeting minimum standards of dietary diversity for lactating mothers is a challenge in many developing countries, including Ethiopia. As a result, the purpose of this study was to evaluate dietary diversity and associated factors among breastfeeding mothers. Method: A community-based cross-sectional study was conducted. A multistage sampling technique was used to get a total of 665 lactating mothers from their kebeles. Face-to-face interviews with a structured questionnaire were used to collect data. Data was entered into Epidata version 3.1 and exported to the Statistical Package for the Social Sciences version 23.0 for analysis. Bivariate and multivariable logistic regression models were used to identify the important predictors of maternal dietary diversity. Variables having p < 0.25 in bivariate analysis were fitted to multivariate analysis. The odds ratio, P-value < 0.05, and 95% CI were computed to show the association of variables. Result: A total of 665 lactating women participated, with a response rate of 96.2%. Only 163 (24.5 %) mothers satisfied the minimal dietary diversity criteria. Mothers' dietary diversity was significantly associated with their education status [AOR 5.173 (2.132-12.552)], head of household [AOR 3.822 (2.290-6.378)], family size [AOR 5.358 (2.838-10.116)], and meal frequency [AOR 3.379 (1.789-6.380). Conclusion: One in every four mothers met the dietary diversity standard. Concerned bodies should consider ensuring large-scale interventions that focus on the identified factors to improve dietary diversity practices.